Francis Bacon - Ades, Dawn; Bowness, Alan; Cieszkowski, Krzysztof; Durham, Andrew; Forge, Andrew; Tate gallery, London (London : Tate Gallery London Thames and Hudson London, 1985)
Bacon began his public career as a painter in 1944 with Three Studies for Figures at the Base of a Crucifixion, the first work in this major retrospective exhibition. All the works in the exhibition, and many more, are reproduced in full colour. Introductory essays have been written by Dawn Ades, the art historian, and by Andrew Forge, the artist, who for many years has been Dean of the School of Art, Yale University, and is a member of the board of directors of the American Academy in Rome. The book also contains an essay on Bacon's painting technique by Andrew Durham and an extensive select bibliography by Krzysztof Cieszkowski, both of The Tate Gallery.
bibliog., filmog. p. 239-246
Engels
Published by orderof the Trustees 1985 for the exhibition of 22 May - 18 August 1985 (Francis Bacon, Tate gallery, London)
boek
Keywords: Bacon, Francis